HUBUNGAN ANTARA KORUPSI DENGAN PENANAMAN MODAL ASING: STUDI KASUS ENAM NEGARA ASEAN: 1997-2005 - Setyadharma, Andryan (Journal of Indonesian Economy and Business, 2007)
The corruption remains significant and unfair barriers to trade and economic1 Terima kasih kepada reviewer atas masukan yang sangat berharga untuk penyempurnaan tulisan ini.development in many countries. These practices increase costs, decrease fair competitionand represent a significant deterrent to foreign investment. Previous studies have showedthat corruption tends to have negative impact on foreign direct investment (FDI) but onlyfew studies have investigated the possibility of effects in the opposite direction. Thispaper attempts to find the relationship between corruption and FDI with two ways:assess the effect of inflows of FDI, as a measure of trade openness, on corruption at thecountry level and also attempts to see the effect of corruption on FDI. It conductsregression analysis on a cross section of six ASEAN countries over the period 1997 to2005 and controls for some other variables likely to impact on corruption as well as FDI.The result shows that thereâs significant impact of corruption on inflows of FDI, and inopposite indicated that inflows of FDI is significant with the lower level of corruption insix ASEAN countries.Keywords: Korupsi, Penanaman Modal Asing, ASEAN